STRATEGI PEMBANGUNAN BUDAYA KEAGAMAAN MODERAT DAN INKLUSIF DI SEKOLAH: Upaya Mencegah Radikalisme dan Intoleransi - Adib, M. Afiqul (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2024)
This study aims to explore the urgency and strategies for building a moderate and inclusive religious culture in schools. Using a literature research method, the data collection technique involves identifying, collecting, classifying, and validating relevant literature, while the data analysis technique includes content analysis, source criticism, synthesis of findings, and drawing conclusions to understand the urgency of building a moderate and inclusive religious culture in school. This study identifies the challenges of radicalism and intolerance as the main reasons for the importance of this initiative. The results show that building a moderate and inclusive religious culture in schools is highly urgent in addressing these challenges. Schools that have successfully implemented such programs have shown improvements in interfaith harmony, appreciation of diversity, and the development of more tolerant student characters. The recommendations include enhancing teacher training, developing a more inclusive curriculum, and strengthening collaboration between schools, parents, and the community. This study is expected to serve as a reference for policymakers and education practitioners in developing educational programs that support moderation and inclusiveness in the school environment. In conclusion, building a moderate and inclusive religious culture in schools not only helps prevent radicalism and intolerance but also promotes a more harmonious educational environment and supports the growth of more open and tolerant student characters.